Filosofi Paku dalam Kepemimpinan Pendidikan Islam - Senang Senang; Hani Adi Wijono (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
Leaders are servants for those they lead, a leader must be able to carry out their duties, fulfill the aspirations and needs of those they lead, while the nail philosophy is a new paradigm in Islamic education leadership to shape the personality of a leader who is ready to carry out his duties and can understand his position. and society, in Islam it is explained that a leader must have characteristics, namely a) knowledgeable, creative initiative, sensitive, open-minded and always responsive, b). Act fairly, honestly and consistently, c). Responsible, d). Selective of information, e). Always give a warning, f). Able to provide instructions and directions, g). Likes to discuss, h). Istiqomah and tough stance, i). Happy to do good, j). Always willing to lighten the burden of others, k). Creative and trusting, l). Have a competitive spirit, m). Aesthetics, good personality and neat appearance, n). Always harmonious and professional in action, o). Disciplined and productive. A leader will face various types of wood (society), which cannot be forced. Leaders must be able to be the mediating nail, the binder or binder between different communities.